A Genetic Analysis of Tumor Progression in Drosophila Identifies the Cohesin Complex as a Suppressor of Individual and Collective Cell Invasion. - Canales Coutiño, B.; Cornhill, Z.E.; Couto, A.; Mack, N.A.; Rusu, A.D.; Nagarajan, U.; Fan, Y.N.; Hadjicharalambous, M.R.; Castellanos Uribe, M.; Burrows, A.; Lourdusamy, A.; Rahman, R.; et al. (iScience, 2020)
Metastasis is the leading cause of death for patients with cancer. Consequently it is imperative that we improve our understanding of the molecular mechanisms that underlie progression of tumor growth toward malignancy. Advances in genome characterization technologies have been very successful in identifying commonly mutated or misregulated genes in a variety of human cancers. However, the difficulty in evaluating whether these candidates drive tumor progression remains a major challenge. Using the genetic amenability of Drosophila melanogaster we generated tumors with specific genotypes in the living animal and carried out a detailed systematic loss-of-function analysis to identify conserved genes that enhance or suppress epithelial tumor progression. This enabled the discovery of functional cooperative regulators of invasion and the establishment of a network of conserved invasion suppressors. This includes constituents of the cohesin complex, whose loss of function either promotes individual or collective cell invasion, depending on the severity of effect on cohesin complex function.